Efisiensi Belanja Publik Untuk Meningkatkan Anggaran Lingkungan - Yoesgiantoro, Donny (Jurnal Kebijakan Ekonomi, 2014)
The purpose of this research is to provide recommendations to government in taking efficiency measures on public spending in order to increase budget allocation for the environment. The data used are secondary data, obtained from the Central Bureau of Statistics and the Ministry of Finance of the Government of Indonesia as well as The World Bank. The research method employed is guantitative descriptive approach. Result shows that in the period of 2005-2014, the average spending growth rate is eguivalent with nominal GDP growth rate. However, the growth of spending on Goods and Services is well above higher than that of nominal GDP, reflecting inefficient spending allocation. Our calculation shows that Goods and Services spending has saving potential of IDR 22,6 trillion, which half of the amount sourced from efficiency of spending on Maintenance Expenditure. Such amountcould significantiy enlarge the spending for the environment, particularly for spending on pollution handling.